FACTORS AFFECTING ON MUSLIM CLOTH PURCHASE DECISION IN NARATHIWAT, THAILAND (Journal of Technology and Operations Management, 2020)
The main intention of this research is to get to know the marketing mix (product, price, place and promotion) issues deliberating on Muslim cloth purchasing decision. The participants of this study were 400 consumers in Narathiwat province. Descriptive statistics such as percentage, frequency, and mean are applied to describe the demographic features of the participants. In Addition, inferential statistics namely; Pearson’s Correlation Coefficient is applied to determine the effect of marketing factors (product, price, place and promotion) on Muslim cloth purchasing decision. The results of the research reported in this study show that product, price, place and promotion are determinant factors that affect the Muslim cloth purchasing decision. Discussions, conclusions and implications of the study are inferred in details.